种废旧电路板资源化处理装置和方法 (2018)
本发明提供种废旧电路板资源化处理装置和方法，主要包括破碎机、自还原熔炼炉、罗茨鼓风机、及烟气处理装置，所述自还原熔炼炉主要由熔炼炉、熔炼喷枪、直升烟道、旋风分离器、燃烧换热塔组成，熔炼炉顶部设有加料口、保温枪口、取样口，直升烟道与旋风分离器入口连接，旋风分离器出口连接燃烧换热塔，燃烧换热塔内部设有空气换热器，燃烧换热塔上部设有热空气出口通过管道与进入熔炼炉的熔炼喷枪连接。本发明通过设备改造及工艺优化，以回收的碳粒作为还原剂、回收的高温工艺气体作为热量，两者相结合，有效提高有价金属的回收率，同时减少系统烟气量，节约能源，降低污染。 The invention provides a recycling treatment device and method of waste circuit boards. The recycling treatment device of waste circuit boards mainly comprises a crushing machine, a self-reduction smelting furnace, a Roots blower and an exhaust gas treatment device. The self-reduction smelting furnace is mainly composed of a smelting furnace body, a smelting spray gun, a vertically lifting flue, a cyclone separator and a combustion heat exchange tower, wherein the top of the smelting furnace body is provided with a charging port, a heat preservation gun port and a sampling port; the vertically lifting flue is connected with an inlet of the cyclone separator; an outlet of the cyclone separator is connected with the combustion heat exchange tower;